A Role for PP1/NIPP1 in Steering Migration of Human Cancer Cells - Martin-Granados, Cristina (Public Library of Science, 2012)
Electrical gradients are present in many developing and regenerating tissues and around tumours. Mimicking endogenous electric fields in vitro has profound effects on the behaviour of many cell types. Intriguingly, specific cell types migrate cathodally, others anodally and some polarise with their long axis perpendicular to the electric vector. These striking phenomena are likely to have in vivo relevance since one of the determining factors during cancer metastasis is the ability to switch between attractive and repulsive migration in response to extracellular guidance stimuli. We present evidence that the cervical cancer cell line HeLa migrates cathodally in a direct current electric field of physiological intensity, while the strongly metastatic prostate cancer cell line PC-3-M migrates anodally. Notably, genetic disruption of protein serine/threonine phosphatase-1 (PP1) and its regulator NIPP1 decrease directional migration in these cell lines. Conversely, the inducible expression of NIPP1 switched the directional response of HeLa cells from cathodal to slightly anodal in a PP1-dependent manner. Remarkably, induction of a hyperactive PP1/NIPP1 holoenzyme, further shifted directional migration towards the anode. We show that PP1 association with NIPP1 upregulates signalling by the GTPase Cdc42 and demonstrate that pharmacological inhibition of Cdc42 in cells overexpressing NIPP1 recovered cathodal migration. Taken together, we provide the first evidence for regulation of directional cell migration by NIPP1. In addition, we identify PP1/NIPP1 as a novel molecular compass that controls directed cell migration via upregulation of Cdc42 signalling and suggest a way by which PP1/NIPP1 may contribute to the migratory properties of cancer cells.